Recruitment in Romanian education – exploratory research of grading, transparency and GDPR - Apetrăcheoae, Alexandra; Gavriluță, Cristina (Technium Social Sciences Journal, 2023)
The purpose of the article is to outline and analyse recruitment in the Romanian education system, its instruments of communication and follow-up, its legal frame and methodologies, its results, and how they are disseminated in order to protect the human resource and the professional image of the teaching staff, find solutions for a better recruitment communication and provide ideas of improving the capability of the system in finding flaws and adapting to the educational and social needs. So, we have documented the communication site for the grades, from the users` end and correlated it with the methodology’s main aspects regarding the communication, then exported a database with the grades from the two main examinations of tenure from 2019 (inspection and theoretical examination) for 30.018 candidates to compare the grades with the public and mass-media perception of the marks. This article is important also for following the status quo of the nowadays recruitment and acknowledging the situation, the cause for the lack of centralized data, and the improvement that can be made to better the educational policies. Our research pointed out great discrepancies between the inspection grades and the theoretical exam grades, some GDRP blind spots, greater protection for students than for teachers even if that means publishing securitized data of the teachers obtained during their period as students, a lack of contextual communication that adversely affects the teachers' image, impossibility to follow the candidates track up to occupying the position taken that makes recruitment in educational system unpredictable and uncorrectable.